ANALISIS KEMISKINAN DAN FAKTOR YANG MEMPENGARUHINYA KASUS : DKI JAKARTA, 2006-2010 - , DINI A DEWANDANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Poverty is one of the biggest economic which is complex and multidimentional because of that, it is important is finding solution to eliminate or at least to reduce poverty. This study is aimed to analize how and how much the influence of GRDP, Human Development Index and Education to the poverty in DKI Jakarta from 2006-2010 The test result simultaneously shows that, totally, independent variable together can point itâs influence to the poverty. And R-squared value of 0,8869 which means 88,69% the poverty variable can be explained by independent variable. While the rest, the 11,31%, explained by other factors outside of the model. Research results show GRDP variable negatively and significantly influence the poverty in DKI Jakarta. Human Development Index negatively and significantly influence the poverty. And Education (illiteracy and dropping out of school at the senior high school) variable positively and significantly influence the poverty in DKI Jakarta.